Botanical and chemical composition of fallow lands grazed by sheep under extensive conditions - Glowacz K.; Niznikowski R.; Popielarczyk D.; Strzelec E.; Lozicki A.; Klimaszewski K.; Poleszczuk O. (Nutritional and foraging ecology of sheep and goats, 2009)
The research was conducted on the 50-hectare fallow land in north-western part of Wielkopolskie Voivodeship, Poland, grazed for 12 years and in 2006 by 200 ewes of Polish heath sheep Wrzosówka. The pasture yield, botanical and chemical composition of herbage in the vegetation period has been analysed. Between June and July the pasture yield and the content of chemical composition in dry matter (except the crude protein only) appeared to be highest. In case of fodder quality, the highest nutritional value was observed at the beginning of the vegetation period in May. Running to the end of the season both the pasture yield and chemical composition (except the micro- and macroelements) have been decreasing, that indicates the need to consider this relationship in proposing of the proper stocking rate.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)